2021
DOI: 10.3390/cancers13102409
|View full text |Cite
|
Sign up to set email alerts
|

Reflector-Guided Localisation of Non-Palpable Breast Lesions: A Prospective Evaluation of the SAVI SCOUT® System

Abstract: Wire-guided localisation (WGL) has been the mainstay for localising non-palpable breast lesions before excision. Due to its limitations, various wireless alternatives have been developed. In this prospective study, we evaluate the role of radiation-free wireless localisation using the SAVI SCOUT® system at the London Breast Institute. A total of 72 reflectors were deployed in 67 consecutive patients undergoing breast conserving surgery for non-palpable breast lesions. The mean interval between deployment and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…It has been found to be at least non-inferior to WGL in terms of successful localisation and margin positivity rates. In addition, the device was reported to have minimal MRI void artefacts (<5 mm), in addition to good surgeon, patient and radiologist acceptability [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found to be at least non-inferior to WGL in terms of successful localisation and margin positivity rates. In addition, the device was reported to have minimal MRI void artefacts (<5 mm), in addition to good surgeon, patient and radiologist acceptability [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant difference in re-excision rates when comparing Magseed with WGL [ 10 , 12 ]. However, our pooled analysis of SAVI SCOUT performance reported that the use of the device was associated with a significant reduction in the re-excision rates compared with WGL in subgroup analysis [ 9 , 11 , 46 ]. However, this requires further validation in adequately powered prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a distance of 2 mm from the tumor margin was considered adequate for ductal carcinoma in situ (DCIS) [13][14][15][16][17][18]. Table 2 shows the overview of the methods used in non-palpable tumors to mark and remove the area of interest in conservative breast surgery [19][20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the use of handheld superparamagnetic devices, such as MagSeed or the Guiding-Marker System, have provided an accurate and reliable localization method in BCS with favorable surgical outcomes [20][21][22] (Table 2). Other alternative, non-radioactive, wire-free localization methods, developed to increase the likelihood of complete tumor removal, include intra-operative ultrasound guidance [23], the LOCalizer radio-frequency identification (RFID) system [24,25], reflector-guided localization through SAVI-SCOUT [26,27], and fluorescence detection after intralesional indocyanine green (ICG) solution injection [113] or intravenous administration was used [28] (Table 2).…”
Section: Preoperative Surgical Planning and Intraoperative Margin Ass...mentioning
confidence: 99%
“…It can be deployed inside the lesions the day before surgery. The Savi-Scout system is another non-wire and non-radioactive alternative technique; it uses a micro-impulse infrared radar to localize the lesions and is particularly useful for patients that need MRI examinations during follow-up, without artifacts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%